Respostas histológicas, bioquímicas e imuno-histoquímica de ratos diabéticos com periodontite tratados com terapia fotodinâmica antimicrobiana - Barin, Luisa Machado (2017)
The present thesis is structured in two animal experimental studies, presented as article that investigated the effects of methylene blue (MB) photosensitizer (Fs) solubilized in ethanol on antimicrobial photodynamic therapy (aPDT) as adjuvant treatment in scaling and root planing (SRP) in the periodontal disease (PD), with or without the involvement of diabetes mellitus (DM). The first article evaluated the systemic and local tissue responses generated by this new Fs in the presence of DM. In addition, it was verified the relationship of vascular endothelial growth factor (VEGF) in the PD advance and repair processes. Eighty Wistar rats received intraperitoneal injection of streptozotocin and after 14 days some rats received ligadure in the mandibular right first molar for experimental induction of PD. The experimental groups were NC (negative control, no PD); PC (positive control, with PD and without treatment); SRP (with PD and SRP); aPDT I (with PD and SRP + aPDT + MB solubilized in water) and aPDT II (with PD and SRP + aPDT + MB solubilized in ethanol). After 7 days, ligadures were removed and animals were treated, then euthanized at 7 and 15 days, and samples collected for biochemical, histological and immunohistochemical evaluation. At 7 and 15 days, the aPDT II group showed lower inflammatory and VEGF intensities, lower blood vessel numbers (only 7 days) and lower oxidative damage (as well as the NC group when reaching 15 days) when compared to the SRP group. The aPDT II demonstrated no statistically significant differences in relation to the aPDT I. It was concluded that the aPDT II was able to facilitate and accelerate the periodontal tissue repair in the short-term and has the potential for periodontal treatment in patients with diabetes allowing faster repairing responses. The aPDT presented additional benefits when compared to SRP alone. The intensity of VEGF was higher in diabetic rats with PD and may have greater influence during advance process of PD. The second study evaluated the responses in the periodontal tissues generated by the same protocol, but in systemically healthy rats. One hundred and twenty Wistar rats were randomized and divided into the same experimental groups as the previous study. The PD was also ligature-induced, remaining for 7 days, then the animals were treated and euthanized at 7, 15 and 30 days. Samples were collected for histological and immunohistochemical evaluation. Treated groups showed lower inflammatory and VEGF intensities when compared to the CP group. Treated groups presented similar responses, however cases of inflammatory absence were observed only in aPDT at 7 days. Interestingly, only aPDT II at 30 days revealed almost total absence of inflammatory infiltration.It was concluded that aPDT provided better responses to periodontal tissue, found by the lower inflammatory degree when compared to SRP in the short-term and the aPDT II demonstrated a greater long-term repair capacity. The highest expression of VEGF was observed in PC, being related to the PD progression.